Application of Contextual Teaching and Learning Using Power Point in Improving Learning Outcomes of Light Properties in Grade IV Students SDN 12 Palu - Murniasih, Ni Putu; Hatibe, Amiruddin; Suleman, Samsurizal M. (Jurnal Riset Pendidikan MIPA, 2020)
Teachers strive to improve student learning outcomes in science subjects through the use of approaches to classroom learning. As for the chosen approach to improve learning outcomes, foster a spirit of learning, diligence, and respect for each other is the approach of contextual teaching and learning (CTL) using power points. The study aims to: 1) describe the implementation of contextual teaching and learning using power points to improve the learning outcomes of light properties in grade IV students at SDN 12 Palu (2) describing increased learning outcomes on the properties of light in grade IV students at SDN 12 Palu through the application of contextual teaching and learning using power points. The research method uses the classroom action research design Mc. Taggart, consisting of 4 stages, namely planning, implementation, observation, and reflection. The research location is at SDN 12 Palu. The research subjects (n = 24) consisting of 13 male students and 11 female students. Data retrieval techniques using observation methods and tests. Data analysis is conducted with qualitative and quantitative data analysis. The results showed that students' activity in Cycle I gained 71.33% or enough category, increasing in cycles of II 86.66% or very good category. Learning activities through the results of observation of teacher skills on cycle I, obtained 76% or good, and cycle II 90.66% or very good. Student learning data for the classical absorbent (DSK) cycle I (63%) and cycle II (80%). For the classical learning (KBK) cycle I (58%) and cycle II (83%). Based on these results, it was concluded that the implementation of contextual teaching and learning using power points can increase the activity and outcomes of science in class IV SDN 12 Palu.